A Methodological Approach for Quantizing Trust from Human Behavior for Content-Driven Websites - Kohli, Shruti; Singal, Himani (International Journal of Sensors Wireless Communications and Control, 2015)
Trust is a psychological factor with subjective properties and hence is very difficult to measure or quantify. Literary assessment on Trust shows that till now researchers have mainly focused on entity-centric issues such as authentication, integrity, reputation, confidentiality, nature and use of information being exchanged but does not consider user behavior for quantizing TRUST. Trust is an inherent virtue, which can be perceived differently by different user/consumer for the same context. This artifact is an endeavor to aggregate users’ behavior over content-driven websites to deduce their prowess of Trust for the former and hence provide a scientific and practical approach for measuring and quantizing Trust. The main aim is to discern which of the users’ attitudinal factors captured by Web Analytics tools can be used to appropriately estimate Trust value for information led websites.
Keywords: User satisfaction